Environmental Law Strategy to Overcome the Waste Accumulation Crisis: Mandala By Pass Case Study - Sianturi, Berliana Grace Devali; Simajuntak, Agtha Sofia; Firman, Al; Pasaribu, Yana Sebha; Nainggolan, Gaby Agustina; Saragih, Jekson; Trisna, Wulan Ayu; Manurung, Yunita Tri Carnova; Ramadhan, Taufiq (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Waste is one of the problems faced by society. The existence of waste is undesirable if it is related to factors of cleanliness, health, comfort and beauty (aesthetics). Factors that influence the environment are the problem of waste disposal and management. Currently, humans don't really care about the environment, there are many people around them who care enough about the state of the environment to create a large accumulation of rubbish in the mandala by pass area. In the accumulation of waste that occurs in the Mandala By Pass area, organic and inorganic waste is often found. The Mandala By Pass community is a densely populated settlement and inevitably produces a lot of waste. The purpose of this research is to find out Environmental Law Strategies for Overcoming the Waste Accumulation Crisis: Mandala By Pass Case Study. Minister of Home Affairs Regulation Number 33 of 2010 concerning Waste Management Guidelines (Permendagri No. 33/2010) is the main legal basis for dealing with waste problems in Indonesia. This Minister of Home Affairs Regulation contains various strategies and policies that can be implemented to overcome the waste accumulation crisis on the Mandala Bypass. The waste accumulation crisis on the Mandala Bypass is a serious environmental issue.